El cumplimiento de los estándares de aprendizaje de comunicación oral en el segundo nivel de la Escuela de Educación Básica “Luis Cordero” del barrio Anchiliví, cantón Salcedo en el año lectivo 2014 – 2015 - Barriga Almachi, Blanca Jeaneth (2015)
New educational challenges and the application of learning standards in the new Curriculum Reform reflects that teachers are in constant training in the four areas of basic education studies; This research is carried out in the area of Language and Literature in the development of macro skill listening this means didactic activities for teaching-learning process in oral communication and discover the flaws which are in the Second Level, so apply qualitative research methods which reflected difficulties in abstraction and expression of general ideas that contain reading in general. This research will contribute with learning activities that strengthen the knowledge to achieve a quality education and warmth awakening in the student's desire to study.